Successful treatment of transplant-associated thrombotic microangiopathy with iptacopan: a non-adult case study - Bao, Shijie; Huang, Kaikai; Huang, Xiao; Zhu, Huamin; Sun, Zhiqiang (Frontiers in Immunology, 2025)
Transplant-associated thrombotic microangiopathy (TA-TMA) is a severe complication of hematopoietic stem cell transplantation (HSCT), characterized by microangiopathic hemolytic anemia, thrombocytopenia, microthrombosis, and multi-organ dysfunction. Mortality rates range from 50% to 90%, with higher rates observed in high-risk patients. The pathogenesis of TA-TMA involves abnormal activation of the complement system—particularly of the alternative pathway—resulting in endothelial injury and microthrombosis. We present the case of a 17-year-old man with high-risk TA-TMA who achieved a favorable outcome following the oral administration of the factor B inhibitor iptacopan. The patient exhibited significant improvements in laboratory markers, including reductions in lactate dehydrogenase, urine protein/creatinine ratio, and C5b-9 levels, along with recovery of platelet counts and haptoglobin levels. This case highlights the potential efficacy of iptacopan in the management of TA-TMA, particularly in high-risk patients, and suggests that complement factor B inhibition may offer a promising therapeutic strategy for this challenging condition.